Hottentot, Bushman, Kaffir: Taxonomic Tendencies in Nineteenth-Century Racial Iconography (Nordic Journal of African Studies, 1996)
Hottentot, Bushman, Kaffir: Taxonomic Tendencies in Nineteenth-Century Racial Iconography